2011
DOI: 10.1371/journal.pone.0028011
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Repression of Cdc25B by IER5 Inhibits the Proliferation of Leukemic Progenitor Cells through NF-YB and p300 in Acute Myeloid Leukemia

Abstract: The immediately-early response gene 5 (IER5) has been reported to be induced by γ-ray irradiation and to play a role in the induction of cell death caused by radiation. We previously identified IER5 as one of the 2,3,4-tribromo-3-methyl-1-phenylphospholane 1-oxide (TMPP)-induced transcriptional responses in AML cells, using microarrays that encompassed the entire human genome. However, the biochemical pathway and mechanisms of IER5 function in regulation of the cell cycle remain unclear. In this study, we inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 34 publications
4
39
0
Order By: Relevance
“…High expression is associated with resistance against the antiproliferative effect of PI3K-Akt-mTOR inhibitors [89], but the molecular mechanisms behind this effect are not known. Inhibition of this isoform seems to reduce AML cell line proliferation through effects on NF-YB and p300 [88]; whereas in other cells growth inhibition is seen only with combined Cyclin D1 and CDC25B inhibition [84]. These regulatory events thus represent a link between CDC25 and the NF-YB system that consist of the three subunits NF-YA, NF-YB and NF-YC; this system seems to contribute to carcinogenesis for several human malignancies [94].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High expression is associated with resistance against the antiproliferative effect of PI3K-Akt-mTOR inhibitors [89], but the molecular mechanisms behind this effect are not known. Inhibition of this isoform seems to reduce AML cell line proliferation through effects on NF-YB and p300 [88]; whereas in other cells growth inhibition is seen only with combined Cyclin D1 and CDC25B inhibition [84]. These regulatory events thus represent a link between CDC25 and the NF-YB system that consist of the three subunits NF-YA, NF-YB and NF-YC; this system seems to contribute to carcinogenesis for several human malignancies [94].…”
Section: Resultsmentioning
confidence: 99%
“…The most important studies are presented in detail in Table 1 [49,[83][84][85][86][87][88][89][90][91], but it should be emphasized that several of these studies are relatively small, describe observations mainly in AML cell lines or used methodological strategies that would not be regarded as optimal today. Thus, knowledge about CDC25 in human AML is in our opinion incomplete, but despite this CDC25 should be regarded as a possible therapeutic target in human AML.…”
Section: Biological Functions Of Cdc25 In Human Amlmentioning
confidence: 99%
“…However, the partial overlap in expression between the two groups (Fig 6) suggest that other resistance mechanisms probably also are operative. Previous studies have demonstrated that (i) overexpression of the immediate-early response gene 5 (IER5) decreases AML cell proliferation as well as CDC25B expression (Nakamura et al, 2011); and (ii) the forkhead box M1 (FOXM1) transcription factor is an important cell cycle regulator that increases the levels of several proteins involved in regulation of cell cycle progression, including CDC25B (Nakamura et al, 2010). We therefore investigated whether there were any significant associations between CDC25B, IER5 and FOXM1 gene expression, and we detected weak but highly significant correlations between IER5 (Pearson r = 0Á4456, P = 0Á0015), as well as FOXM1 (Pearson r = 0Á4116, P = 0Á0037) and CDC25B expression.…”
Section: Analysis Of Global Gene Expression Profiles Identified Cdc25mentioning
confidence: 99%
“…Nevertheless, the association between CDC25B, IER5 and FOXM1 expression and pharmacological resistance in AML needs to be further explored in future studies. The role of CDC25B in human AML has only been investigated in experimental studies (Didier et al, 2008;Nakamura et al, 2010Nakamura et al, , 2011. CDC25B is important for initiation of the cell cycle and its degradation is necessary for correct exit from mitosis (Thomas et al, 2010).…”
Section: Pi3k-mtor Inhibition In Human Amlmentioning
confidence: 99%
“…In contrast to c-Fos and c-Jun, the role of IER5 has not been described yet. However, it has been shown that IER5 encodes a protein that acts as a regulator of cell proliferation [43], and thus may be involved in tissue remodeling after strokes.…”
Section: Introductionmentioning
confidence: 99%